Study protocol of a systematic review and qualitative evidence synthesis using two different approaches: Healthcare related needs and desires of older people with post-stroke aphasia - Nadine Janis Pohontsch; Maria-Inti Metzendorf; Thorsten Meyer; Yvonne Eisenmann; Verena Leve; Veronika Lentsch (BMJ Open)
Introduction Stroke is a frequent disease in the older population of Western Europe with aphasia as a common consequence. Aphasia is known to impede targeting treatment to individual patients’ needs and therefore may reduce treatment success. In Germany, the postacute care of patients who had stroke is provided by different healthcare institutions of different sectors (rehabilitation, nursing and primary care) with substantial difficulties to coordinate services. We will conduct two qualitative evidence syntheses (QESs) aiming at exploring distinct healthcare needs and desires of older people living with poststroke aphasia. We thereby hope to support the development of integrated care models based on needs of patients who are very restricted to communicate them. Since various methods of QESs exist, the aim of the study embedding the two QESs was to determine if findings differ according to the approach used.Methods and analysis We will conduct two QESs by using metaethnography (ME) and thematic synthesis (ThS) independently to synthesise the findings of primary qualitative studies. The main differences between these two methods are the underlying epistemologies (idealism (ME) vs realism (ThS)) and the type of research question (emerging (ME) vs fixed (ThS)).We will search seven bibliographical databases. Inclusion criteria comprise: patients with poststroke aphasia, aged 65 years and older, studies in German/English, all types of qualitative studies concerning needs and desires related to healthcare or the healthcare system. The protocol was registered in the International Prospective Register of Systematic Reviews, follows Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines and includes three items from the Enhancing Transparency in Reporting the synthesis of Qualitative Research checklist.Ethics and dissemination Ethical approval is not required. Findings will be published in a peer-reviewed journal and presented on national conferences.